(untitled) (Journal of University of Babylon for Engineering Sciences, 2022)
This project promotes the creation of a nanofiber fabric made of polystyrene nanofibers reinforced with locally produced kaolin nanoparticles. An electrospinning procedure was used to create the overlapping fibers. The kaolin particles employed in this study underwent an X-ray test, and the outcome matched that of the typical test. The AFM results demonstrated that the nano-kaolin has a high fineness (1.5 nanometers), good surface area, and a high tolerance factor 6, in addition to other desirable properties. Kaolin nanoparticles in various ratios were utilized to evaluate the effect of kaolin on the hydrophobic behavior of polystyrene nanofibers. The results showed that the produced nanofibers could self-clean since they were hydrophobic (could not absorb water) and had a contact angle of 87 degrees, which increased after adding kaolin nanoparticles (139 o) . This study also looked into how solution characteristics like solution concentration and viscosity affected the diameters of the resulting fibers. The impact of nano Kaolin concentrations on the diameters of the resulting fibers was examined for the ideal concentration (0.12 g/ml), which was achieved because free-bead nanofibers were produced. This concentration was previously determined with the stability of the other parameters. The findings demonstrated that as kaolin nanoparticle concentration rises, so do nanofiber diameters because rising solution viscosities increase the number of nanofibers reinforced with kaolin nanoparticles. Additionally, wetting angle rises until it reaches 139 degrees.